Leaching of lead sulfide with nitric acid - Oh, J.K.; Lee, J.Y.; Lee, H.Y.; Kim, S.G.; Han, C.; Shin, J.K. (1999)
Galena, lead sulfide, is leached with nitric acid in order to prepare higher value-added products such as lead nitrate, lead carbonate, lead basic carbonate, etc. Leaching behavior has varied with the concentration of nitric acid. At the lower concentration of nitric acid, galena is dissolved into lead nitrate and hydrogen sulfide. However, at the higher concentration of nitric acid, galena is not dissolved but it is changed into lead sulfate as precipitate. The leaching efficiency is strongly dependent upon temperature and nitric acid concentration. The optimal conditions are found to be 40°C and 4？8 N nitric acid where about 95% of lead can be dissolved from lead sulfide. ？ 1999 Taylor & Francis Group, LLC.